Karakteristik Mikrobiologis, Fisik dan kimia Digesta Tikus Diabetes Induksi STZ-NA yang diberi Diet Kefir Kombinasi Susu Kambing dan Susu Kedelai - , Fafa Nurdyansyah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of this research was to evaluate changing in prebiotic component (fructo-oligosaccharides/FOS and rafinose) during kefir fermentation of goat-andsoymilk combination and its addition effect on growth of tested bacteria in MRS broth media, and also to evaluate goat-and-soymilk kefir administration on microorganism profile and physico-chemical characteristic of diabetic rats digesta. First stage of the research was 3 kinds of kefir preparation using goat milk (GM), mixture of goat milk : soymilk with 1:1 ratio (GSM), and soymilk (SM). Second stage analysis on each kefir addition effect on E.coli, Bifidobacterium longum, and Lactobacillus acidophillus culture in MRS broth media before enumerated in selective media at 0, 24, and 48 hours. Third stage was in vivo study using 5 groups of rats : Group I was normal rats, Group II was diabetic control rats, while Group III, IV, and V were diabetic rats administered with GM kefir, SM kefir, and GSM kefir, respectively. In the end of treatment period, profile of Lactobacilli, Bifidobacter and E.coli bacteria, short chain fatty acid/SCFA, moisture content, pH, and weight of digesta were analyzed. During kefir fermentation, FOS and rafinose were decrease in all milk kefir. Analysis on tested bacteria indicating utilization selectivity of kefir prebiotic component by Lactobacillus acidophilus, and Bifidbacterium longum which were higher than E. coli at 24 and 48 hours. In vivo study showed that diabetic rats administered with GSM kefir had significantly higher Lactobacilli and Bifidobacter population with lower E.coli compared to diabetic and normal rats, as well as rats administered with GM and SM. Rats administered GSM kefir had digesta with highest SCFA and lowest pH compared to normal, GM, and SM groups. Treatment had no significant effect on digesta weight, while digesta moisture content was lower on GM group. In conclusion, kefir made of goat-andsoymilk combination had high potential as therapeutic functional food for diabetic patients.